Identifikasi Peran Sektor Industri Pengolahan terhadap Perekonomian Sulawesi Selatan dengan Analisis Input Output - Rika Dwi Kurniasih; Yoenus Osman; Fathien Azmy (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
Economic structure of developed region is characterized by increasingly large role of manufacturing and trade sector to sustain the region's economy. The amount of Gross Domestic Product (GDP) of South Sulawesi province shows its economy is getting better for years. GDP value is influenced by main contribution of manufacturing sector and other sectors such as agriculture, trading, and services that make economic developed. To develop manufacturing sector, the government of South Sulawesi needs information that is more detail about how big the share of manufacturing sector to the economic development. This research uses Input Output (IO) matrix for analyzing the economic development of South Sulawesi Province that linkages between manufacturing within its sectors. The result of this analysis, it can be found that there are two sectors have high attractive index and sensitivity degree, that are, chemical goods, paper and other paper or cardboard and products, and printed items. If there are increasing final demand of subsector chemicals goods, the demand of 21 input subsectors will raise too. This fact can influence the whole of economic development in South Sulawesi Province. In addition, this study obtained a multiplier coefficient of income and employment that describe the economic condition of South Sulawesi Province.